EDUKASI DAN SOSIALISASI PENGELOLAAN SAMPAH DI SD TUGUMUKTI KECAMATAN CISARUA KABUPATEN BANDUNG BARAT - Fitra Nurhakim; Sri Lestari; Yunyun Ratna; Rizal Abdul Ghany (ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Community services the persistent issue of waste management in elementary schools, focusing on SD Tugumukti Kecamatan Cisarua Kabupaten Bandung Barat, where low levels of student awareness contribute to improper waste disposal within the school environment. The research aims to enhance students’ understanding and behavior regarding waste sorting through a structured educational program. Using a descriptive method, the study employed observations, interactive learning sessions, games, and pre-test and post-test assessments to analyze changes in students’ knowledge and behavior. The findings indicate a notable improvement in students’ comprehension of waste types and their ability to sort waste correctly, accompanied by observable positive behavioral changes after the intervention. The discussion highlights the alignment of these findings with environmental education theory, emphasizing the importance of experiential learning in shaping pro-environmental behavior. The study concludes that well-designed educational interventions can effectively cultivate environmental awareness among young learners and recommends continuous implementation of environmental education, supported by adequate facilities and active teacher involvement, to sustain long-term behavioral change. Keywords: Waste Management; Environmental Education; Elementary School.